Pembuatan Sistem Informasi Administrasi Pada UD. Satu Saudara Plastik - Kevin Yosi Putra Utama; Yulia Yulia; Silvia Rostianingsih (Jurnal Infra, 2020)
UD Satu Saudara Plastik is a home industry company that manufactures plastic goods. Examples of goods produced are wall clocks, bottle caps, motorcycle mirrors, plastic bottles, and push-steps on motorcycles. Before application development begins, an analysis and design with data flow diagrams and entity relation diagrams. This application is made with HTML, PHP, JavaScript, MySQL database, and Bootstrap. The application made includes customer order features, sales data, customer order status, raw material stock, raw material purchase. The final result of application development is that the application has a master data feature for raw materials, finished materials, positions, supporting, customers, orders, production requests, input costs, so as to produce customer order reports, income statements, raw material stock reports, reports of total orders, order payment report, revenue report. Based on testing, the system can carry out transaction activities such as sales transactions, and reporting activities for UD Satu Saudara Plastik. The results of the questionnaire show for the display application, more than 70% of respondents answered well. For ease of use of the application, 57% of respondents were satisfied. For the suitability of the application with the needs, 57% of respondents were satisfied and 12.5% very satistfied. For the result application is 87.5% of respondents were satisfied, and around 12.5% of respondents felt less satisfied.